Agronegócio da soja no Piauí: região do fazer produtivo - Leal, Manuela Nunes (2013)
The modernization of agriculture and the regionalization of capital in rural and urban areas from soybean agribusiness of Piauí promoted numerous socio-spatial transformations. Phenomenon that begins in the 1970s with the first experiments with the production of soybeans and acquires body in the 1990s, forming over the years a growing region and a production chain structuring. The aim of this study is to analyze the arising socio-spatial transformations of agricultural modernization and restructuring of production from soybean agribusiness Piauí and the formation of a productive region. The methodology used was a review of literature and data collection in organs such as the Instituto Brasileiro de Geografia e Estatística (IBGE) and Fundação Centro de Pesquisa Econômica e Sociais do Piauí (CEPRO). In addition, fieldwork was conducted on farms in the cities of Baixa Grande do Ribeiro, Ribeiro Gonçalves, Sebastião Leal, e Uruçuí. In the field research were interviewed twenty five workers, six ranch owners or managers and four employees of companies that make up the production chain of agribusiness. The capital and its materialization with agribusiness grain in southwestern of Piauí promoted changes in land use, labor relations and implementation of new technologies in the country. The expansion of harvested area, production and average yield improvements in this area shows the producer in the production process restructuring and modernization of agriculture. Thus, consolidated in a region of Piauí make productive managed by large companies and owners of grain that comprise a supply chain increasingly complex and interconnecting new chains such as agribusiness meat.